OPTIMAL RELAY DESIGN OF ZERO FORCING EQUALIZATION FOR MIMO MULTI WIRELESS RELAYING NETWORKS - Apriana Toding (Jurnal Ilmiah Kursor, 2017)
In this paper, we develop the optimal relay design for multiple-input multiple-output (MIMO) multi wireless relaying networks, when we consider the problem of zero-forcing processing is studied for multi-input multi- output multi-relay communication system in which MIMO source-destination pairs communicate simultaneously. It is assumed that due to severe shadowing effects which communication links can be established only with the aid of relay node. The aim is to design the relay amplification matrix to maximize the achievable communication sum- rate through the relay, which in general amplifying-and- forward relaying mechanisms are considered. The zero forcing (ZF) algorithm has studied for a MIMO multi relay network by comparing its performance in terms of bit- error-rate (BER) at destination algorithm. In particular, we investigate its performance with and without using the ZF at the relay. Our results demonstrate that the system performance can be significantly improved by using the ZF algorithm at relay (optimal relay ZF algorithm)